Glucose-lowering therapies in patients with diabetes mellitus and chronic kidney disease - Minara Shamkhalovna Shamkhalova; Ivona Renata Yarek-Martynova; Natalya Petrovna Trubitcyna; Marina Vladimirovna Shestakova (Сахарный диабет)
Expansion of diabetic population (predominantly due to type 2 diabetes mellitus) with chronic kidney disease (CKD) comorbidity constitutes one of the major challenges in modern medicine.Throughout the course of diabetes nephropathy development, from its debut to the terminal stage, survival rate and quality of life are lower than those of other categories of patients. This indicates crucial role of hyperglycemia in accelerated metabolic degradation typical of CKD.Renal disease severely narrows the spectrum of available glucose-lowering agents. Concurrent treatment for hypertension and dyslipidemia, as well as anti-platelet therapy and stimulation of erythropoiesis becomes a complex issue. A creative and patient-oriented approach with clear metabolic and cardiovascular goals should be instrumental in its solution.